Narrative Structure in Short Stories Written by Fifth-Grade Students at SDN Cipanas, Sukabumi City - Idris, M. Taufik; Helmanto, Fachri; Effane, Anne (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to analyze the narrative structure in short stories written by fifth-grade students at SDN Cipanas, Sukabumi City. The research focuses on three fundamental narrative elements: character, conflict, and events. Employing a qualitative approach with content analysis as the primary method, the study is supported by data from classroom observations, interviews, and documentation of students’ written work. The findings reveal that most students were able to present main characters from a first-person perspective, although character development remained superficial. The element of conflict was generally underdeveloped, with many stories depicting routine daily activities lacking narrative tension. Event sequences were organized chronologically but rarely reached a complete narrative structure, including orientation, complication, and resolution. These results suggest that students’ narrative writing skills are still in the early stages of development. The study highlights the need for more structured and creative pedagogical strategies to enhance students’ understanding of cohesive storytelling. It offers practical implications for the improvement of writing instruction in primary education and serves as a reference for further research in the field of narrative literacy. Keywords: narrative structure, short story, character, conflict, events, primary school students